Мікроекономічний підхід до діагностики економічної безпеки підприємства - Васильченко, Олена Олегівна; Vasylchenko, Olena (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: Розглянуто роль та значення мікроекономічної теорії при аналізі поведінки споживачів та виробників на мікрорівні. Продемонстровано практичне застосування мікроекономічних моделей поведінки фірми на ринку з певним типом конкуренції. Доведено необхідність та можливість мікроекономічної теорії відігравати ключову роль у плануванні виробничо-господарської діяльності фірми і формуванні її поведінкової стратегії на ринку задля зміцнення своїх конкурентних позицій. /// EN: The economic security of all subjects of entrepreneurial and other activities is of crucial importance for ensuring the successful functioning of a market economic system. With all the variety of methods and techniques for diagnosing the economic security of an enterprise, almost no attention is paid to the sufficiently weighty theoretical basis that microeconomic theory has today. Research results. The use of a microeconomic approach to explaining various aspects of the activities of microeconomic subjects allows us to show the effectiveness of microeconomic theory and its significant impact on the behavior of both consumers and producers. This approach can also be used to analyze the economic security of an enterprise, as well as to determine the possibilities of its strengthening. The mechanism of applying microeconomic methods in studying the issue of economic security of an enterprise is revealed on the example of the activities of one of the food industry enterprises. The economic security zone of a food factory for the production and sale of bakery products is determined. In order to identify the main ways of its expansion, an analysis of the market in which this enterprise operates was carried out. It was found that the expansion of the economic safety zone of a processing enterprise is influenced by demand, supply and price. It was also proven that the possibility of expanding the economic safety zone is due to the enterprise’s orientation towards the optimal volume of output, the value of which was found out by using microeconomic tools. Conclusions. Modern diagnostics of enterprise activities requires new research tools. Microeconomic theory has developed basic models of firm behavior in conditions of various types of market competition, which can be successfully applied during the analysis of the enterprise’s production and economic activities. This study practically proves the feasibility of using microeconomic techniques not only for diagnostics, but also for planning the enterprise’s activities and developing a strategy for its behavior in difficult conditions of market competition.
Microeconomic approach to diagnostics of an enterprise’s economic security
Keywords: мікроекономічний аналіз; діагностика; економічна безпека підприємства; попит; пропозиція; ціна; типи ринку; монополістична конкуренція; сукупний та граничний підхід; оптимальний обсяг випуску; зона економічної безпеки; microeconomic analysis; diagnostics; economic security of the enterprise; demand; supply; price; market types; monopolistic competition; aggregate and marginal approach; optimal output; economic security zone